A novel tool to predict functional outcomes after robot‐assisted radical prostatectomy and the value of additional surgery for incontinence. (1st October 2020) - Tutolo, Manuela; Bruyneel, Luk; Van der Aa, Frank; Van Damme, Nancy; Van Cleynenbreugel, Ben; Joniau, Steven; Ammirati, Enrico; Vos, Gigi; Briganti, Alberto; De Ridder, Dirk; Everaerts, Wouter; ,
Abstract : Objectives: To develop and validate a model to predict 12‐month continence status after robot‐assisted radical prostatectomy (RARP) from preoperative and 3‐month postoperative data; this model could help in informing patients on their individualised risk of urinary incontinence (UI) after RP in order to choose the best treatment option. Patients and Methods: Data on 9421 patients in 25 Belgian centres were prospectively collected (2009–2016) in a compulsory regional database. The primary outcome was the prediction of continence status, using the International Consultation on Incontinence Urinary Incontinence Short Form (ICIQ‐UI‐SF) at 12‐months after RARP. Linear regression shrinkage was used to assess the association between preoperative 3‐month postoperative characteristics and 12‐month continence status. This association was visualised using nomograms and an online tool. Results: At 12 months, the mean (sd ) score of the ICIQ‐UI‐SF questionnaire was 4.3 (4.7), threefold higher than the mean preoperative score of 1.4. For the preoperative model, high European Association of Urology risk classification for biochemical recurrence (estimate [Est.] 0.606, se 0.165), postoperative radiotherapy (Est. 1.563, se 0.641), lower preoperative European Organisation for Research and Treatment of Cancer quality of life questionnaire 30‐item core (EORCT QLQ‐C30)/quality of life (QoL) score (Est. −0.011, se 0.003), higher preoperative ICIQ‐UI‐SF score (Est 0.214, se 0.018), and older age (Est. 0.058, se 0.009), were associated with a higher 12‐month ICIQ‐UI‐SF score. For the 3‐month model, higher preoperative ICIQ‐UI‐SF score (Est. 0.083, se 0.014), older age (Est. 0.024, se 0.007), lower 3‐month EORCT QLQ‐C30/QoL score (Est. −0.010, se 0.002) and higher 3‐month ICIQ‐UI‐SF score (Est. 0.562, se 0.009) were associated with a higher 12‐month ICIQ‐UI‐SF score. Conclusions: Our models set the stage for a more accurate counselling of patients. In particular, our preoperative model assesses the risk of UI according to preoperative and early postoperative variables. Our postoperative model can identify patients who most likely would not benefit from conservative treatment and should be counselled on continence surgery.